K-pop idolization influence fans' purchase intention - Tan, KaiWen (2024)
As the music industry grows, South Korea is one of the nations that is actively promoting its music abroad. The success of K-pop can be seen when people have come to recognize K-pop culture as their own unique cultural identity especially youths are more easily influenced by K-pop. There is evident from several fan support activities that their idol has holds a particular place in the fandom as many K-pop fans loyal to their idol and start consuming many merchandise or product related to their idol. Therefore, this study will be focusing on how the K-pop idolization influence fans’ purchasing intention and the factors lies within it. This study is being carried out by using quantitative method and the data is gathered by using online survey questionnaire. The questionnaire is obtained from a total of 120 respondents who aged between 18 to 26 years old in Malaysia. Following that, the quantitative data will be statistically analysed to determine how the K-pop idolization influence fans’ purchasing intention and the factors lies within it. The findings show that fans' engagement in spending on merchandise is motivated by their deep emotional attachment to K-pop idols as well as the attractiveness of their persona and appearance. Additionally, social media presence and promotional activities further strengthen fans' willingness to support their favourite K-pop idol by purchasing their merchandise. With this study, industry stakeholders could have an in-depth awareness of these dynamics to optimize marketing tactics and meet the varied requirements and preferences of K-pop fans.